2018
DOI: 10.1002/jcc.25614
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the applicability of density functional tight binding to transition metal ions. Parameterization for nickel with the spin‐polarized DFTB3 model

Abstract: In this work, we explore the applicability and limitations of the current third order density functional tight binding (DFTB3) formalism for treating transition metal ions using nickel as an example. To be consistent with recent parameterization of DFTB3 for copper, the parametrization for nickel is conducted in a spinpolarized formulation and with orbital-resolved Hubbard parameters and their charge derivatives. The performance of the current parameter set is evaluated based on structural and energetic proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 95 publications
(145 reference statements)
1
20
0
Order By: Relevance
“…[103][104][105][106] Until recently, no straightforward parameterization for transition-metals was available, but a recent study for nickel based on DFTB3 showed the feasibility of such an approach. [107] The resulting DFTB structures for a number of nickel complexes compare favorably to available X-ray structures, and an encouraging agreement with the B3LYP/aug-cc-pVTZ reference data was observed.…”
Section: Dftbsupporting
confidence: 54%
“…[103][104][105][106] Until recently, no straightforward parameterization for transition-metals was available, but a recent study for nickel based on DFTB3 showed the feasibility of such an approach. [107] The resulting DFTB structures for a number of nickel complexes compare favorably to available X-ray structures, and an encouraging agreement with the B3LYP/aug-cc-pVTZ reference data was observed.…”
Section: Dftbsupporting
confidence: 54%
“…The highest-level variant (DFTB3) employs a selfconsistent charge treatment including up to third order density fluctuation terms 55,56 and has been parametrized for a number of chemical elements. [58][59][60][61][62] In particular, the element pair-specific parametrization used in all aforementioned methods has complicated the parametrization procedure and only PM6 covers large parts of the periodic table of elements (70 elements). Recently, we have presented a DFTB3 variant, termed GFN-xTB, which mostly follows a global and element-specific parameters only strategy and is parametrized to all elements through radon.…”
Section: Introductionmentioning
confidence: 99%
“…DFTB3 was previously shown to produce good geometries and adequate energy for a wide range of scenarios. It performed well for biomolecular systems [ 61 , 62 , 63 ], systems with metal cations in general [ 29 , 64 , 65 , 66 ], and Ca 2+ specifically [ 67 , 68 ], achieving better energies then DFT calculations with a double-ζ basis set. In both tasks, QM simulation was run in parallel by 10 walkers each sampling for 100 ps thus accumulating 1 ns of QM/MM trajectory.…”
Section: Methodsmentioning
confidence: 99%